Toward an emotional involvement of the reader-subject: the subjective reading of the linguistic autobiography: Exemple of "A Zhuang Girl" by Wei-Wei - DAROUI, Maroua (Journal of Human Sciences, 2025)
The aim of this article is to analyse the contribution of literary reading of Wei-Wei's A Zhuang girl to the professional training of future national education trainers in Algeria. The approach adopted encourages a subjective reading of this autobiographical language through the prism of a dual cognitive and emotional perspective, in order to promote the acquisition of disciplinary and cross-disciplinary skills inherent in the profession of teacher-trainer. In addition to the effectiveness of this approach in supporting learners in their efforts to acquire a deeper understanding of the French.